C/EBPα Regulates Generation of C/EBPβ Isoforms through Activation of Specific Proteolytic Cleavage - Welm, Alana L. (American Society for Microbiology, 1999)
C/EBPα and C/EBPβ are intronless genes that can produce several N-terminally truncated isoforms through the process of alternative translation initiation at downstream AUG codons. C/EBPβ has been reported to produce four isoforms: full-length 38-kDa C/EBPβ, 35-kDa LAP (liver-enriched transcriptional activator protein), 21-kDa LIP (liver-enriched transcriptional inhibitory protein), and a 14-kDa isoform. In this report, we investigated the mechanisms by which C/EBPβ isoforms are generated in the liver and in cultured cells. Using an in vitro translation system, we found that LIP can be generated by two mechanisms: alternative translation and a novel mechanism—specific proteolytic cleavage of full-length C/EBPβ. Studies of mice in which the C/EBPα gene had been deleted (C/EBPα(−/−)) showed that the regulation of C/EBPβ proteolysis is dependent on C/EBPα. The induction of C/EBPα in cultured cells leads to induced cleavage of C/EBPβ to generate the LIP isoform. We characterized the cleavage activity in mouse liver extracts and found that the proteolytic cleavage activity is specific to prenatal and newborn livers, is sensitive to chymostatin, and is completely abolished in C/EBPα(−/−) animals. The lack of cleavage activity in the livers of C/EBPα(−/−) mice correlates with the decreased levels of LIP in the livers of these animals. Analysis of LIP production during liver regeneration showed that, in this system, the transient induction of LIP is dependent on the third AUG codon and most likely involves translational control. We propose that there are two mechanisms by which C/EBPβ isoforms might be generated in the liver and in cultured cells: one that is determined by translation and a second that involves C/EBPα-dependent, specific proteolytic cleavage of full-length C/EBPβ. The latter mechanism implicates C/EBPα in the regulation of posttranslational generation of the dominant negative C/EBPβ isoform, LIP.